Case Report: Two cases of primary pulmonary endobronchial extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue localized in the trachea and bronchus - Sha, Lei; Cai, Meng-Yao; Feng, Min; Dong, Chang (Frontiers in Oncology, 2025)
BackgroundPrimary pulmonary extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) localized in the trachea and bronchus is rare and diagnostically challenging due to nonspecific clinical and radiological features.Case descriptionWe present two cases of primary endobronchial MALT lymphoma incidentally diagnosed via bronchoscopy. We assessed the characteristic bronchoscopic finding of endobronchial MALT lymphoma, radiological examinations and overall treatment strategies.ConclusionThis study highlights the importance of considering endobronchial MALT lymphoma as a potential diagnosis. A thorough bronchoscopic evaluation of the central airways, along with appropriate biopsy of suspicious lesions, is crucial. Endobronchial MALT lymphoma should be suspected when targeting multiple widely stalked and smooth submucosal nodules or protrusions, mainly located in the central airways.